1995
DOI: 10.1152/ajpendo.1995.269.5.e948
|View full text |Cite
|
Sign up to set email alerts
|

Use of R-beta-[1-11C]hydroxybutyrate in PET studies of regional cerebral uptake of ketone bodies in humans

Abstract: A method for determining regional cerebral utilization of ketone bodies in humans is described. After a bolus injection of R-beta-[1-11C]hydroxybutyrate, the time course of the tracer in the brain was measured with positron emission tomography in five healthy volunteers. The regional cerebral blood flow was measured separately. The tracer uptake in the brain could be well described by a single rate constant, indicating that the concentration of unmetabolized ketone bodies in the brain is very low and that tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 0 publications
4
57
0
Order By: Relevance
“…4. Plot of the accumulation rate constant (Kket) against [␤-HB]plas for each subject in groups of nondiabetic subjects (s) and IDDM patients (OE) at hyperglycemia and in the group of nondiabetic subjects at normoketonemia (F) studied previously (1). The linear regression line (slope Ϫ0.0025 Ϯ 0.0006, intercept 0.0114 Ϯ 0.0006, and R value 0.76) is also displayed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4. Plot of the accumulation rate constant (Kket) against [␤-HB]plas for each subject in groups of nondiabetic subjects (s) and IDDM patients (OE) at hyperglycemia and in the group of nondiabetic subjects at normoketonemia (F) studied previously (1). The linear regression line (slope Ϫ0.0025 Ϯ 0.0006, intercept 0.0114 Ϯ 0.0006, and R value 0.76) is also displayed.…”
Section: Discussionmentioning
confidence: 99%
“…3. Plot of the cerebral metabolic rate of ketone body utilization (CMRket, obtained with the 2-tissue compartment model) against ␤-HB concentration in plasma ([␤-HB]plas) for each subject in the groups of nondiabetic subjects (s) and IDDM patients (OE) at hyperglycemia and in the group of nondiabetic subjects at normoketonemia (F) studied previously (1). The displayed regression line is calculated with all data in the previous and present studies; it has the slope 7.9 Ϯ 0.5, the intercept 0.39 Ϯ 0.54, and the R value of 0.97.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies of lightly anesthetized rodents, brain ketone consumption has been reported to be small, at approximately 3% of total (Hawkins et al, 1986). This contrasts to measurements made in humans, performed through [ 11 C]-β-hydroxybutyrate (BHB) positron emission tomography (PET) (Blomqvist et al, 1995) and AV difference measurements (Owen et al, 1965;Hasselbalch et al, 1994Hasselbalch et al, , 1996. In fasted and nonfasted human studies, ketones have been reported to provide a substantially larger fraction of brain oxidative metabolism, up to 50% of energy production in 3-week fasted obese subjects.…”
mentioning
confidence: 94%